Delivering intensive, individualized interventions to children and youth with learning and behavioral disabilities - Tankersley, Melody; Cook, Bryan G.; Landrum, Timothy J. (Bingley, U.K. : Emerald Publishing Limited, 2022)
Intensive, individualized interventions are certainly the hallmark promise of special education. In a multi-tiered system of supports (MTSS), tier 3 interventions are the most intensive and require individualized delivery to address the learning and behavioral needs of students who are most often identified for special education services. MTSS, such as Responsiveness to Intervention (RTI) and Positive Behavioral Interventions and Supports (PBIS), are comprised of universal assessment, progress monitoring, and databased decision-making as intervention is implemented with increasing intensity and individualization based on the needs of the learner. The chapters in this volume cover a broad range of topics that address issues surrounding the identification of students who need the most intensive intervention, intensive intervention features and delivery considerations, behavioral interventions, academic interventions, and preservice teacher preparation. The authors of the chapters are recognized as international experts on these topics and provide specific recommendations that are based on research evidence as well as discuss considerations for future enhancement of multi-tiered systems of supports and intensive interventions. This is a contemporary resource for teachers, administrators, and teacher-educators who are charged with delivering special education and/or supporting those who do.
Chapter 1. Delivering intensive, individualized interventions to children and youth with learning and behavioral disabilities: Introduction to the volume / Melody Tankersley, Bryan G. Cook, and Timothy J. Landrum -- Chapter 2. Identifying students with intensive academic and behavioral needs / Shanna E. Hirsch, Melissa K. Driver, Michelle Hinzman-Ferris, and Allison Bruhn -- Chapter 3. When standard approaches fail: Advances in the conceptualization and delivery of intensive interventions / Nathan A. Stevenson -- Chapter 4. Essential features of intensive, individualized (tier 3) interventions / Kathleen Lynne Lane, Eric Allen Common, Mark Matthew Buckman, and Grant Allen -- Chapter 5. The role of function in behavioral intervention / John Umbreit and Jolenea B. Ferro -- Chapter 6. Treatment integrity and intensity: Critical considerations for delivering individualized interventions / Robin S. Codding, Melissa Collier-Meek, and Emily DeFouw -- Chapter 7. Conducting systematic reviews of the literature: Guidance for quality appraisal / Kathleen Lynne Lane, Eric Alan Common, David James Royer, and Wendy Peia Oakes -- Chapter 8. An examination of the text characteristics of an early reading book series: Implications for providing intensive practice with connected text / Jill Allor, Devin Kearns, Miriam Ortiz, and Carlin Conner -- Chapter 9. Intensive reading interventions for adolescents and the challenges of comorbid reading and behavioral difficulties / Michael Solis and John W. McKenna -- Chapter 10. Intensive intervention for students with mathematics learning difficulties / Minyi Shih Dennis -- Chapter 11. Developing preservice teacher knowledge and confidence of functional assessment-based interventions / Wendy Peia Oakes.
Includes bibliographical references and index.
Keywords: Children with disabilities -- Education; Behavior disorders in children; Special education; Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs